Gestão coletiva de direitos no audiovisual: o direito a remuneração de roteiristas e diretores pela exibição pública de obras cinematográficas no Brasil - Macedo, Marina Band (2019)
This dissertation purpose is to explore why the Brazilian audiovisual sector does not use the collective management of rights to guarantee the remuneration of screenwriters and film directors for the public exhibition of their cinematographic works. The research argument holds that the non-use of the collective management of rights in the Brazilian audiovisual sector is related to the missing provision of a procedure for the constitution of a Collection and Distribution Office in the legislation in the same way that it occurs at the musical sector; and a lack of knowledge and effective representation of the directors and screenwriters during the drafting and voting of the changes regard Collective Rights Management at the Copyright bill. The applicability of the study is in the proposition of alternative ways of managing rights that guarantee the remuneration of screenwriters and directors for the public exhibition of cinematographic works and may benefit the audiovisual productive chain due to the scarce bibliography on the subject in Brazil and the possibility of being converted into public policies for the sector, as well as institutional material on the subject, thus revealing this study practical relevance